BAFF Blockade Attenuates Inflammatory Responses and Intestinal Barrier Dysfunction in a Murine Endotoxemia Model - Quan, Runze; Chen, Chaoyue; Yan, Wei; Zhang, Ying; Zhao, Xi; Fu, Yu (Frontiers in Immunology, 2020)
B cell-activating factor (BAFF) production is increased in septic patients. However, the specific role of BAFF in sepsis remains unknown. This study was designed to investigate the expression and function of BAFF in an experimental endotoxemia model and to identify the potential mechanisms. We established an endotoxemia mouse (6–8 weeks, 20–22 g) model by administering 30 mg/kg lipopolysaccharide (LPS). BAFF levels in the circulating system and organ tissues were measured 4 and 8 h after LPS injection. Survival rates in the endotoxemia mice were monitored for 72 h after BAFF blockade. The effects of BAFF blockade on systemic and local inflammation, organ injuries, and intestinal barrier function were also evaluated 4 h after LPS treatment. BAFF production was systemically and locally elevated after LPS challenge. BAFF blockade improved the survival rate, systemic inflammation, and multi-organ injuries. Moreover, BAFF blockade attenuated both intestinal inflammation and impaired intestinal permeability. BAFF blockade upregulated ZO-1 and occludin protein levels via the NF-κB/MLCK/MLC signaling pathway. These results suggested that BAFF blockade protects against lethal endotoxemia at least partially by alleviating inflammation, multi-organ injuries, and improving intestinal barrier function and provides a novel focus for further research on sepsis and experimental evidence for clinical therapy.